Elements for an argumentative ethics - Monsalve Solórzano, Alfonso (Estudios de Filosofía, 1994)
Perelman’s idea of value is applied as a notion that, though obscure, makes agreement possible within the universal audience (the set of present day adult reasonable individuals), in order to, on the one hand, propose an ethics that overcomes the limitations of Rawls’ liberalism, founded on Kantian constructivism, and, on the other hand, criticize Habermas’ purely dialogical model as being scarcely applicable. Nevertheless, this is achieved while conserving the contributions made by both philosophers in solving the ethical and political conflicts of the present world. Argumentative ethics, as here presented, asserts an agreement between rival claims of justice as being the result both of strategic and communicative action, based on a conception of moral progress, understood as a point of no retum which embodies the conception of human rights and their development in contemporary society.